2020
DOI: 10.1186/s40945-020-00081-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical examination factors that predict delayed recovery in individuals with concussion

Abstract: Background Risk factors for prolonged recovery after concussion have been well researched, but specific objective clinical examination findings have not. This study examined whether clinical examination results could predict delayed recovery (DR) in individuals with concussion diagnosis. A secondary aim explored the influence of early examination on individual prognosis. Methods The study was a retrospective, observational cohort des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Our study had a low proportion of participants with a history of depression at 4% ( n = 5), whereas a general population of adults would be expected to be nearer to 10% (DSM-5). This low percentage is supported by a previous study that found that athletes scored higher in the mental toughness category [ 28 ]. Mental toughness is known to be linked to developmental experiences, and sports participation offers challenges and commitment [ 28 ].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Our study had a low proportion of participants with a history of depression at 4% ( n = 5), whereas a general population of adults would be expected to be nearer to 10% (DSM-5). This low percentage is supported by a previous study that found that athletes scored higher in the mental toughness category [ 28 ]. Mental toughness is known to be linked to developmental experiences, and sports participation offers challenges and commitment [ 28 ].…”
Section: Discussionsupporting
confidence: 72%
“…This low percentage is supported by a previous study that found that athletes scored higher in the mental toughness category [28]. Mental toughness is known to be linked to developmental experiences, and sports participation offers challenges and commitment [28]. In the scientific literature, mental toughness is evaluated through interviews and mental toughness inventories [28].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Traumatic Brain Injury (TBI) is estimated to affect 790 per 100,000 New Zealanders every year ( 1 ) and is a leading cause of disability in young adults. Symptoms of dizziness and imbalance are common and are among the risk factors predicting prolonged recovery ( 2 , 3 ). These symptoms are often attributed to dysfunction of the vestibular system ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Complaints of persistent imbalance are commonly reported after mTBI, with ~28% of people still reporting problems more than a year following their injury ( 4 ). Visual- and vestibular-related symptoms that occur after mTBI and can be predictive of long-lasting persistent symptoms well after the initial injury ( 5 7 ). However, recent evidence suggests that those with balance deficits due to a chronic mTBI (persistent mTBI symptoms >3 months after initial injury) have largely normal peripheral vestibular and ocular motor function ( 8 ).…”
Section: Introductionmentioning
confidence: 99%